p38 phosphorylates Rb on Ser567 by a novel, cell cycle-independent mechanism that triggers Rb-Hdm2 interaction and apoptosis - Delston, Rachel B. (2010)
The retinoblastoma protein (Rb) inhibits both cell division and apoptosis, but the mechanism by which Rb alternatively regulates these divergent outcomes remains poorly understood. Cyclin dependent kinases (Cdks) promote cell division by phosphorylating and reversibly inactivating Rb by a hierarchical series of phosphorylation events and sequential conformational changes. The stress-regulated mitogen activated protein kinase (MAPK) p38 also phosphorylates Rb, but it does so in a cell cycle-independent manner that is associated with apoptosis rather than with cell division. Here, we show that p38 phosphorylates Rb by a novel mechanism that is distinct from that of Cdks. p38 bypasses the cell cycle-associated hierarchical phosphorylation and directly phosphorylates Rb on Ser567, which is not phosphorylated during the normal cell cycle. Phosphorylation by p38, but not Cdks, triggers an interaction between Rb and the human homologue of murine double minute 2 (Hdm2), leading to degradation of Rb, release of E2F1 and cell death. These findings provide a mechanistic explanation for how Rb regulates cell division and apoptosis through different kinases, and reveal how Hdm2 may functionally link the tumor suppressors Rb and p53.